A meta‐analysis on the effectiveness of homofermentative and heterofermentative lactic acid bacteria for corn silage - Blajman, Jesica E. (2018)
Aims: This meta‐analysis aims to assess the effect of lactic acid bacteria (LAB) inoculation on fermentation parameters, microbiological composition and aerobic stability of corn silage. Methods and Results: Databases (PubMed, ScienceDirect and Scopus) were searched from 1980 to 2017. The criteria for inclusion were: randomized and controlled experiments using corn silage and published in peer‐reviewed journals. The meta‐analysis showed that LAB supplementation increased pH, acetate and propionate concentrations, and decreased acid detergent fibre, water‐soluble carbohydrates and ammoniacal nitrogen (NH3‐N) compared to controls in the pooled raw mean difference random effect model. In addition, inoculation reduced counts of yeasts and moulds, increased LAB counts and markedly improved aerobic stability in corn silage. However, results indicated that the effect of inoculants may differ depending on the administration of homofermentative or heterofermentative LAB. Conclusions: For the development of functional bacterial inoculants, both types of LAB should be used.